Analysis of the Causes of Burnout Syndrome Among Workers in the Logistics Industry Sector at PT. X Batam City in 2025 - Jayati, Trisna; Rizky Permata, Hening (Rifa'Institute, 2025)
Introduction: Burnout is an emotional condition that occurs when a person experiences physical and mental exhaustion due to increased responsibilities at work. Objective: The purpose of this study was to analyze the causes of Burnout Syndrome among workers at PT. X, Batam City, in 2025. Method: The research method used was quantitative research with a cross-sectional approach. The sampling technique used total sampling with a sample of 38 workers at PT. X, Batam City. Data were obtained using Chi-square test analysis. Result and Discussion: The results showed that PT. X, Batam City had a high workload category (55%), good work environment category (95%), and moderate worker Burnout Syndrome category (55%). Based on the analysis results, workload (p-value = 0.047), work environment (p-value = 0.043), and work stress (p-value = 0.019) were found to be significant. Conclusion: The conclusion of this study is that there is a significant relationship between workload, work environment, and work stress with Burnout Syndrome at PT. X, Batam City. This research suggests that companies should manage employee burnout well to prevent the occurrence of Burnout Syndrome.